Serum response factor is essential for endometrial function and prevention of inflammatory fibrosis - Ryan M. Marquardt; Sara A. Grimm; San-Pin Wu; Peter F. Lais; Shu-Yun Li; Xin Xu; Erin Smithberger; David Cunefare; Charan Ganta; David Olson; Eunhee M. Jeong; Jae-Wook Jeong; et al. (Proceedings of the National Academy of Sciences, 2025)
Pregnancy requires a supportive uterine environment facilitated by steroid hormone–regulated differentiation of endometrial stromal fibroblasts into decidual cells and tight control of inflammation. Serum response factor (SRF) is a widely expressed transcription factor essential for mesenchymal cell growth and differentiation with noted roles in hormonal regulation of muscle tissues but little characterization in reproductive organs. Here, we reveal that endometrial SRF is dysregulated in human endometriosis and is critical for female reproductive success in mice through regulation of endometrial stromal and epithelial cells. Immunohistochemical analysis identified decreased endometrial SRF expression in infertile endometriosis patient tissues. RNAi-based SRF knockdown in human endometrial stromal cells resulted in disrupted cytoskeletal structure, viability, and decidual response. Conditional Srf knockout mice (Srf d/d ) generated using the Pgr Cre were infertile with implantation failure, lack of decidual response, and development of severe endometrial fibrosis. Single-cell RNA sequencing identified dramatic changes in Srf d/d endometrial cell populations including large-scale myeloid immune cell infiltration. Srf d/d stromal fibroblasts displayed aberrant cytoskeletal and extracellular matrix gene expression and downregulation of genes important for decidual growth response. Srf -deficient epithelial cells displayed the most prominent dysregulation, strongly overexpressing estrogenic innate inflammatory genes including C3 and Lcn2 and fibrogenic genes Mmp7 and Fbln1 , all of which paralleled patterns in human endometriosis patient data that we identified through comparative analysis using a published single-cell atlas. These results demonstrate the profound impact of SRF on endometrial homeostasis with relevance to human endometriosis–related infertility.